Experimental study on the effect of key mix design parameters on shrinkage and cracking resistance of dry-mix shotcrete. (21st February 2022) - Menu, Bruce; Pepin Beaudet, Alexandre; Jolin, Marc; Bissonnette, Benoit
Highlights: SF, FA, polymer, SRA, and CRA reduce shotcrete rebound while improving porosity and placement quality. The effect of cement content on the total shrinkage of dry-mix shotcrete is relatively small. Adding SF or a combination of SF/FA to dry-mix shotcrete increases the potential for shrinkage cracking. Polymer, SRA, and CRA reduce total free shrinkage and improve cracking resistance of dry-mix shotcrete. The setup used yields high-quality shotcrete rings that comply with the AASHTO T 334 ring test standard. Abstract: Shotcrete is used in a wide variety of repair applications that usually results in concrete elements having a large surface area. After curing, this large exposed surface area-to-volume ratio can lead to a non-uniform moisture distribution in the in-place shotcrete which will create differential drying shrinkage. The shrinkage and potential subsequent cracking depend on the selected material proportions and the curing regime. The three-fold focus of this study is to investigate (i) the possibility of improving the shrinkage performance of dry-mix shotcrete by optimizing the coarse aggregate and cement content, (ii) the influence of silica fume ( SF ) and a combined SF and fly ash ( FA ), (iii) and the influence of polymer, shrinkage-reducing admixture (SRA) and crack-reducing admixture (CRA) on shrinkage and cracking resistance of dry-mix shotcrete using a modified restrained shrinkage ring test . The results indicate that SF, FA, polymer, SRA, or CRA have the potential of reducing shotcrete rebound as well as improve their porosity and placement quality. The results also show that the effect of cement content on shrinkage is relatively small. The addition of SF or combined SF/FA increased the cracking potential of the dry-mix shotcrete mixtures while the addition of polymer, SRA, and CRA reduced the total free shrinkage and increased the cracking resistance of shotcrete. The results further indicate that shrinkage and cracking resistance of shotcrete are closely related to mixture parameters.